Current opportunities to improve outcomes of COVID-19 infection prevention and course in patients with lymphoproliferative diseases (regional analysis) - Ch. Kh. Valiakhmetova; E. I. Siraeva (Онкогематология)
Background. Impaired immune response in patients with lymphoproliferative diseases (LPD) can lead to severe COVID-19 infection and significantly affect survival by increasing the risk of death. The effectiveness of vaccines may be reduced in people with compromised immune system function. Sequential vaccination does not ensure the production of sufficient antibodies in patients with hematological malignancies. Patients with LPD need additional measures to prevent COVID-19 infection.The high efficacy of monoclonal antibodies combinations to the SARS-CoV-2 S-protein for COVID-19 infection prevention and treatment has been shown in clinical trials. The complex use of active and passive immunization in immunocompromised patients requires confirmation in real clinical practice.Aim. A comparative analysis of COVID-19 infection severity and prevention effectiveness in patients with LPD.Materials and methods. The retrospective analysis included 200 patients with LPD who received induction therapy in R epublican Clinical Oncological Dispensary (Ufa) from 01.09.2021 to 01.09.2022. All patients received the Gam-COVID-Vac vaccine (Sputnik V, National Research Center for Epidemiology and Microbiology named after Honorary Academician N . F . Gamaleya, Ministry of Health of Russia). Patients were divided 1:1 into 2 groups matched by gender, age, LPD immunophenotype, history of previous treatment. In the 1st group, in order to pre-exposure prophylaxis of COVID-19 infection, in addition to the Gam-COVID-Vac vaccine, 2 recombinant monoclonal antibodies were administered – 150 mg tixagevimab + 150 mg cilgavimab intramuscularly. In both groups, the frequency of COVID-19 infection, the frequency of viral pneumonias identified and not identified as COVID-19 infection, the number of hospitalizations due to infection, and overall mortality were analyzed. SARS-CoV-2 positive tests results, symptoms of acute respiratory disease, the frequency of pneumonia, the number of hospitalizations for viral pneumonias, and the total mortality over a period of 4 months were recorded in the ProMed electronic medical system.Results. The patient groups were balanced by age (55 and 58 years, respectively), gender, pretreatment and use of anti-CD20 monoclonal antibodies (67 and 68 %), spectrum of nosologies: Hodgkin’s lymphoma in the 1st group was diagnosed in 21 %, in the 2nd – in 20 % of patients; diffuse large B-cell lymphoma – in 36 and 35 % of patients, respectively; follicular lymphoma – in 16 % of patients in each group; marginal zone lymphoma – in 14 % of patients in each group; mantle cell lymphoma – in 2 % of patients in each group; chronic lymphocytic leukemia – in 8 and 9 % of patients, respectively; peripheral T-cell lymphoma – in 3 % of patients in each group.The combination of tixagevimab 150 mg + cilgavimab 150 mg reduced the incidence of COVID-19 infection by almost 12 times: 59 % of patients in the 2nd group developed COVID-19 infection, while in the 1st group it was observed only in 5 % of patients, in addition, in patients of the 1st group, the infection was mild in more than half of the cases, while in the 2nd group, 2 / 3 of the patients developed viral pneumonia.The frequency of hospitalizations due to the severe course of COVID-19 infection in the 1st group was 9 times lower – 3 % versus 28 % in the 2nd group.The use of tixagevimab 150 mg + cilgavimab 150 mg combination reduced the frequency of deaths by 30 times: in the 1st group, 1 (1 %) patient died, in the 2nd group – 30 (30 %). No mortality from COVID-19 infection has been reported with the combination of tixagevimab 150 mg + cilgavimab 150 mg.The only lethal outcome in the 1st group was due to the progression of oncohematological disease. Among the 30 patients who died in 2nd group, almost half (46 %) died due to COVID-19 infection. In 2nd group, 3 (3 %) patients died from decompensation of concomitant diseases, which indirectly indicates a decrease in the risk of death with the use of additional prophylaxis in LPD patients.Conclusion. Additional prophylaxis of COVID-19 infection in oncohematological patients with the combination of monoclonal antibodies tixagevimab 150 mg + cilgavimab 150 mg (Evusheld) significantly improves outcomes by reducing the risk of infection, severe course and death from COVID-19. Reducing these risks allows patients to receive complete treatment course, without violation of the time intervals between courses, ensuring the expected overall survival.COVID-19 infection in any clinical form, including asymptomatic, delays antitumor treatment, which reduces overall survival. The use of Evusheld also reduces the risk of death from other comorbid conditions.